The technique of «Subliminal verbal suggestion for the treatment of [pseudo]obsessions» - Danilevska, N. V. (Zaporozhye Medical Journal, 2016)
[Pseudo]obsessions therapy in patients with endogenous diseases of schizophrenic round accompanied with difficulties, caused by both psycho etio pathogenetic features of the disease. Disadvantages of the existing methods of therapy are associated with therapeutic conflict between two nosologies. Aim: to develop and test etiopsychopathogenetic technique "Subliminal verbal suggestion for the treatment of [pseudo]obsessions" as a subsidiary method of treatment of schizophrenia patients with [pseudo] obsessions in the structure of the disease. Methods and results. 137 patients who underwent hospital treatment 65 schizophrenia patients (F20) with the [pseudo]obsessive symptoms in the structure of the disease were examined on the basis of Public Health Institution «Regional clinical mental hospital» of the Zaporizhzhian regional council. 30 patients received standard pharmacotherapy (antipsychotic drugs) according to clinical protocols that was combined with proposed technique "Subliminal verbal suggestion for the treatment of [pseudo]obsessions". The comparison group consisted of 35 patients treated with the use of standard pharmacotherapy: antipsychotic drugs. The next methods were used: medical history assessment, follow-up, clinical-psychopathological, psychodiagnostic. "Subliminal verbal suggestion for the treatment of [pseudo]obsessions" technique was developed. This technique is a combination of suggestion in the waking state and neurolinguistic programming, implemented with specially compiled auditory complex listening. The main therapeutic component s realized through the subthreshold perception of the verbal formulas that are unavailable to awareness. The technique consists of two components – primary and secondary, and three stages. The methodology was tested, its therapeutic efficacy was confirmed. Conclusion. "Subliminal verbal suggestion for the treatment of [pseudo]obsessions" technique was developed as a subsidiary method of the schizophrenia patients with [pseudo]obsessions in the structure of the disease treatment. Proven therapeutic efficiency of the developed technique, was confirmed by clinical psychopathological and psychodiagnostic study. Patients who underwent treatment with the use of "Subliminal verbal suggestion for the treatment of [pseudo]obsessions" techniques in addition to standard therapy had a significant reduction in the severity and frequency of the [pseudo]obsessions, improved smoother speech and thinking, reduce anxiety, mood enhancement, normalization of lifestyle, the violation of which was associated with a [pseudo]obsessions, compared to the comparison group.